BENTUK, MAKNA LOGIS, DAN PERAN KONJUNGSI DALAM VIDEO TANGGAPAN ANIES BASWEDAN TERHADAP HASIL PILPRES INDONESIA 2024 DI YOUTUBE - Darmawan, Adhitya; Rohmah, Nada Humaida; Sumarlam (IAIN Surakarta, 2024)
This research focuses on revealing the form, logical meaning, and role of conjunctions from the discourse of presidential candidate Anies Bawedan towards the results of the 2024 Indonesian presidential election. The focus of this research is done by using a discourse analysis approach through the lens of Systemic Functional Linguistics, especially on conjunctions. The conjunction theory used belongs to Martin and Rose in Wiratno. The paradigm of this research is qualitative research because the nature of reality of this research is plural and constructed holistically based on its context. The data in this study were collected using purposive sampling technique. The method used in this research is the listening method (accessing and watching a video on YouTube entitled “Pesan Anies Baswedan Usai Kalah Quick Count, Minta Pendukung Relawan Lawan Kecurangan